Development: the Malaysian experience - Soltani, Fakhreddin; Jawan, Jayum; Talib, Ahmad Tarmizi (Macrothink Institute, 2014)
Politics in Malaysia is dominated by ethnic considerations; hence, the most critical challenge of development in the country has been the issue of national unity. The Malaysian government has attempted to include all ethnic groups in the process of development regardless of their ethnicity or religion especially since the ethnic riots of 1969. Therefore, the Malaysian government designed economic programs such as the New Economic Policy (NEP) and New Economic Model (NEM) to facilitate this process through state- oriented policies and also include all ethnic groups in the process of development. In fact, Malaysia has followed non-conventional theories of development because of the role of government in the development process. This article seeks to explain the ambitious grand programs of the Malaysian government and demonstrate how these programs have followed non-conventional theories of development.